Iklim Sangat Berpengaruh Terhadap Risiko Produksi Usahatani Bawang Merah (Allium Ascalonicum L) - WIDYANTARA, WAYAN; YASA, NENGAH SUDIRTA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2013)
Normal 0 false false false EN-US X-NONE X-NONE st1\:*{behavior:url(#ieooui) } /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} ABSTRACT The Climate Influential Effect to the Production Risk of Shallots Farming Onion is one of the commodoties widely used in the Indonesian households, ranging from as a spice to herbal medicine. This means that onion has important value in society. Generally, farmer grow onion during dry season; however, in Kintamani District, Bangli Regency, Bali Province, they grow onion during wet season as well as during dry season. This study aimed at identifying the risk of farm enterprise of onion, and the factors which contributed to such a risk. The result of analysis showed that the farm enterprice of onion was more risky than that during wet season. Climate was also found to contribute to the risk of the farm enterprice of onion. Keywords : onio), production risk, climate.